Research of Rural Architecture in Aegean Region: Villages of Bayindir - Akyüz Levi, Eti; Taşcı, Burcu; Taşcı, Burcu (Yıldız Teknik Üniversitesi, 2017)
Rural architecture and settlements occupy an important place in conservation discipline. In this study, the architectural pattern of Karahayit, Gaziler, and Kabaagac-the three villages affiliated to Zeytinova, Bayindir, Izmir-is examined and evaluated, and proposals regarding the future of the villages are made. The villages are documented through field surveys and literature reviews and are evaluated in a comparative study. This study is primarily based on the field surveys that determined in-situ conditions about villages. Villages are settlements that are isolated from the center and have limited transportation possibilities. Moreover, many people migrated to cities from the villages due to limitations of education and employment, resulting in the dilapidation of many of the houses as no one live in them. Settlement has taken form in agreement with the topography; the houses have inclined towards the valley and the scenery. Olive cultivation and cattle breeding are the main sources of living. The mosque and laundry buildings are among the important buildings. It is seen that various interventions were made in the houses during the usage. The physical sustainability of the houses must be ensured in integration with sustainable social, economic, and living conditions. The following measures seem appropriate: the houses should be adapted for current living conditions; a technical contribution should be made during the repair work; and the houses should be expropriated and utilized for touristic functions. The maintenance of villages should be evaluated in the context of rural development. Furthermore, production and marketing possibilities should be developed, and welfare activities should be increased. Finally, ecotourism as a means in rural development should be considered.
Keywords: Bayindir; Gaziler; Kabaagac; Karahayit; rural architecture; village